2003
DOI: 10.1099/ijs.0.02666-0
|View full text |Cite
|
Sign up to set email alerts
|

rDNA sequence analyses of Streptococcus dysgalactiae subsp. equisimilis isolates from pigs

Abstract: The nucleotide sequences of 16S and 23S rRNA genes (rDNA) were determined for 11 isolates of Streptococcus dysgalactiae subsp. equisimilis from slaughtered pigs with endocarditis, arthritis or lymphadenitis and strain ATCC 35666, designated as a strain of subspecies equisimilis. The sequences of each of the genes were compared phylogenetically with the corresponding sequences of S. dysgalactiae subsp. dysgalactiae ATCC 43078 T and ATCC 27957, which were also determined in this study. Based on the 16S rDNA anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…Eleven isolates of SDSE from pigs slaughtered in Japan with endocarditis, arthritis, or lymphadenitis were characterized on the basis of nucleotide sequences of 16S rRNA and 23S rRNA genes [58]. Our colleagues have completed whole-genome analysis of the pig-derived SDSE L1 strain, finding high homology between this L1 strain and human SDSE strains (GGS_124 and RE378; unpublished data).…”
Section: Perspectives Concerning Emerging Infectious Diseasementioning
confidence: 99%
“…Eleven isolates of SDSE from pigs slaughtered in Japan with endocarditis, arthritis, or lymphadenitis were characterized on the basis of nucleotide sequences of 16S rRNA and 23S rRNA genes [58]. Our colleagues have completed whole-genome analysis of the pig-derived SDSE L1 strain, finding high homology between this L1 strain and human SDSE strains (GGS_124 and RE378; unpublished data).…”
Section: Perspectives Concerning Emerging Infectious Diseasementioning
confidence: 99%
“…According to enzymatic profiles, these strains were recommended as the subspecies S. dysgalactiae subsp. equisimilis although it needed more proofs (Nomoto et al, 2006;Kawata et al, 2003). Three-fifth and four-fifth healthy sturgeons died after being challenged with the dosage of 4 × 10 8 CFU of sturgeon's isolates and LD50 value of one representative isolate for crucian carps was 2.45 × 10 8 -5.54 × 10 8 CFU even after passage through them three times.…”
Section: Tablementioning
confidence: 99%
“…Three cases of iatrogenic SDSE infection following transfusion of platelet concentrates were described [19], as well as cases of nosocomial infections [30]. It was found that most patients with invasive infections caused by SDSE were suffering from additional disorders, especially with cardiovascular diseases of atherosclerotic etiology, diabetes, obesity, [72,73], dogs [74], camels [75], cattle [44] and sea otters [76]. Marked differences have been found between SDSE strains deriving from humans and animals [44,73].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that most patients with invasive infections caused by SDSE were suffering from additional disorders, especially with cardiovascular diseases of atherosclerotic etiology, diabetes, obesity, [72,73], dogs [74], camels [75], cattle [44] and sea otters [76]. Marked differences have been found between SDSE strains deriving from humans and animals [44,73]. Kawata et al [73] discovered no streptokinase activity on human plasminogen in any of 11 SDSE strains isolated from pigs, such activity being one of the most important distinctive features of this bacterium [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation